Legal Protection of Telecommunication Service Customers' Personal Data as Trade Secrets in Merger And Acquisition Processes Based on Positive Law in Indonesia - Rossame, Amelia; Rosadi, Sinta Dewi; Permata, Rika Ratna (Publikasi Indonesia, 2023)
The fast advancement of information and communication technology has had a positive influence on society. The free and open transmission of knowledge is the ideal condition for its application. Meanwhile, information technology itself serves as a channel for information dissemination. Customer data received by telecommunications service providers is a trade secret of the corporation since it has economic worth, is confidential, and is kept confidential. Customer personal data, on the other hand, is sensitive and deemed harmful since telecommunications service providers indirectly gain from someone's privacy. This paper will compare the legal framework if there is a legal conflict between personal data and trade secrets based on positive law in Indonesia that applies the GDPR principles to the personal data protection system adopted by other nations, take, for example, the United States, Europe, also Australia. In accordance with the attached case, namely a data breach by Optus, an Australian telecommunications company, the author wishes to examine it within the scope of positive law in Indonesia by comparing legal settlements that have been implemented in Australia, so that if a data breach occurs in Indonesian territory as a result of telecommunications industry mergers and acquisitions, the author will be able to analyze it within the scope of positive law in Indonesia and can be a basis for answering questions regarding legal protection and accountability.